2023
DOI: 10.1186/s13287-023-03438-w
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells shift the pro-inflammatory phenotype of neutrophils to ameliorate acute lung injury

Abstract: Background Mesenchymal stem cell (MSC) treatment plays a major role in the management of acute lung injury (ALI), and neutrophils are the initial line of defense against ALI. However, the effect of MSCs on neutrophils in ALI remains mostly unknown. Methods We investigated the characteristics of neutrophils in lung tissue of ALI mice induced by lipopolysaccharide after treatment with MSCs using single-cell RNA sequencing. Neutrophils separated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The improved healing in of the PRP+MSCs group may have been assisted by reduced inflammatory cell infiltration. Previous studies have shown that MSCs may reduce inflammatory cell infiltration in tissues and may facilitate the healing process [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The improved healing in of the PRP+MSCs group may have been assisted by reduced inflammatory cell infiltration. Previous studies have shown that MSCs may reduce inflammatory cell infiltration in tissues and may facilitate the healing process [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…These pro-inflammatory factors are particularly abundant in immune chemotaxis. In the same year, the research team also reported that they used scRNA-Seq to identify four distinct lung B cell clusters in ALI mice (Feng et al, 2020). Furthermore, they demonstrated that the classification of B cell clusters was independent of whether MSC treatment was administered.…”
Section: Interaction Between Mscs and Immune Systemmentioning
confidence: 98%
“…In 2023, they investigated neutrophil characteristics in ALI mouse lung tissue after MSC treatment using single-cell RNA sequencing. The study revealed six clusters of neutrophils, including activated, aged, and circulatory subtypes ( Feng et al, 2023 ). Activated neutrophils exhibited higher chemotaxis, reactive oxygen species (ROS) production, and NADPH oxidase scores compared to aged neutrophils.…”
Section: Application Of Scs In the Direction Of Mscs Biological Functionmentioning
confidence: 99%
“…ALI after burns is a common and serious complication of burns, and its mechanisms are complex and varied: (1) Burns lead to direct tissue destruction and necrosis, releasing large amounts of intracellular and extracellular biologically active molecules, such as cytokines, inflammatory mediators, and oxygen free radicals [ 28 ], these substances activate immune cells and other inflammatory mediators, causing an inflammatory response in the lungs; (2) After burns, the body undergoes a systemic inflammatory response, prompting the release of inflammatory mediators such as interleukin-1 (IL-1), tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6) in the bloodstream, and these inflammatory mediators can spread rapidly through the bloodstream to the lungs, activating inflammatory cells in the lungs and leading to inflammatory reactions in the lung tissue [ 29 ]; (3) Burns cause damage to the vascular endothelium and an increase in vascular permeability, leading to impaired pulmonary microcirculation, which can cause leakage of intravascular fluid and the formation of pulmonary edema, as well as making it easier for inflammatory mediators to penetrate into the lung tissue [ 30 ]; (4) Burns cause the generation of oxygen free radicals, a highly reactive class of oxidizing molecules produced during tissue hypoxia and reperfusion, which exacerbate the inflammatory response and cause direct damage to cellular and tissue structures [ 31 ]; (5) alveolar surface-active substances (ASASs) are lubricants that help prevent alveolar collapse, and in ALI, inflammation and edema may lead to disruption of ASASs, which may in turn affect respiratory function; (6) in ALI, epithelial and endothelial cells may undergo apoptosis, a controlled process of cell death, and apoptosis may damage lung structures and cause an inflammatory response; (7) The immune system may be abnormally activated in ALI, leading to an excessive inflammatory response and damage to lung tissue. ALI after burn injury is a complex pathophysiologic process that includes direct thermal traumatic effects and a systemic inflammatory response [ 32 , 33 ]. Together, these factors lead to lung inflammation, edema, microthrombosis, and tissue damage, ultimately triggering ALI (Fig.…”
Section: Ali After Burningmentioning
confidence: 99%